A correlation of disease severity and outcome with malnutrition status in adults with COVID-19 - Krishnaswamy, Priyadharshini; L., Ashok M. (International Journal of Advances in Medicine, 2022)
Background: Coronavirus disease 2019 (COVID-19) pathology increases catabolism and depletes the protein stores, causing malnutrition. However, nutrition assessment in COVID-19 is often overlooked in the current pandemic. The Controlling Nutritional Status (CONUT) score is a validated score to assess nutritional status in hospitalized patients. The objective of the study was to estimate malnutrition among hospitalized adult patients with COVID-19 using the - The Controlling Nutritional Status (CONUT) score and study its effect on the disease severity and outcomes. Methods: The study was a retrospective study on 146 patients with COVID-19. The history, demographic details were noted and the following parameters were noted at baseline and time of outcome- COVID-19 disease severity, radiological severity, CONUT score, inflammatory markers- serum LDH, CRP, Ferritin, D-Dimer. The outcome parameters- mortality, duration of hospital stay and severity of disease at outcome were measured. Results: Out of the 146 patients, 84 (57.53%) were male and 62 (42.47%) were female. 97.26% patients had malnutrition at baseline with 42 (28.77%) mild, 70 (47.95%) moderate and 30 (20.55%) severe malnutrition based on CONUT score. The CONUT scores were greater at outcome compared to baseline (p<0.001). Higher grades of malnutrition were associated with greater baseline and outcome disease severity (p<0.001), radiological severity (p<0.001), higher levels of inflammatory markers (p<0.001) and a higher mortality (p<0.001). However, there was no significant difference in duration of hospital stay (p=0.67). Conclusions: Malnutrition results in worse outcomes and greater mortality in COVID-19. Individual tailored nutritional support in the hospitalized COVID-19 patients, can thus potentially improve outcomes.